Polyethylene composition for film

JP7651521B2Active Publication Date: 2025-03-26BASELL POLYOLEFINE GMBH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022129598
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-09-20
Filing Date
2022-08-16
Publication Date
2025-03-26
Estimated Expiration
2039-09-04

Smart Images

  • Figure 0007651521000004
    Figure 0007651521000004
  • Figure 0007651521000001
    Figure 0007651521000001
  • Figure 0007651521000002
    Figure 0007651521000002
Patent Text Reader

Abstract

It is particularly suitable for blown film production due to its balance of bubble stability, processability and dart drop impact strength, 0.948~0.960g / cm 3 and high mechanical properties. The present invention relates to a polyethylene composition particularly suitable for the production of blown films, characterized in that: 1) 0.948~0.960 g / cm 3 density of; 2) MIF / MIP ratio of 20–40; 3) MIF less than 6–15 g / 10 min; 4) HMWcopo index of 0.5 to 3.5; 5) Long-chain branching index (LCBI) of 0.82 or less; 6) η below 150,000 0.02 .
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a 0.948 to 0.960 g / cm 3 and high mechanical properties. In particular, the composition is particularly suitable for blown film production due to its balance of bubble stability, processability and Dart Drop Impact strength.

[0002] The present disclosure also relates to a multi-stage polymerization process for producing said polyethylene composition. [Background technology]

[0003] Polyethylene, especially multimodal polyethylene, is used extensively to produce films by the blown film extrusion process due to its mechanical strength, processability, excellent chemical resistance and low specific weight.

[0004] However, as explained in WO2016206957, existing blown films made of polyethylene have an inadequate balance of mechanical strength, particularly in terms of dart drop impact strength (DDI) and processability. In fact, attempts to obtain high DDI values ​​result in unacceptable deterioration of processability, particularly in terms of bubble stability formed during the blown film extrusion process.

[0005] It has now been discovered that by properly selecting the rheological, thermal and molecular characteristics of the polyethylene composition, an improved balance of the above properties may be achieved.

[0006] In particular, it has been found that the shear viscosity in the molten state and the crystallization time, along with the molecular structure and melt flow index of the polymer, play important roles in determining the above properties. Summary of the Invention

[0007] The present disclosure provides a polyethylene composition having: A) Density 0.960 g / cm3 at 23°C, determined according to ISO 1183-1:2012 3 %. 30 to 70% by weight, preferably 40 to 60% by weight, of ethylene homopolymers or copolymers (homopolymers are preferred) having a melt flow index (MIE) of 130 g / 10 min or less, preferably 120 g / 10 min or less, in particular 50 to 130 g / 10 min, or 55 to 120 g / 10 min, measured at 190° C. under a load of 2.16 kg according to ISO 1133-2:2011; B) 30 to 70% by weight, preferably 40 to 60% by weight, of an ethylene copolymer having a lower MIE value than that of A), preferably a MIE value of less than 0.5 g / 10 min; The amounts of A) and B) are based on the total weight of A)+B); The polyethylene composition has the following characteristics: 1) 0.948-0.960 cm, measured according to ISO 1183-1:2012 at 23°C 3 , preferably 0.949 to 0.958 g / cm 3 density; 2) a MIF / MIP ratio between 20 and 40, in particular between 20 and 38, or between 25 and 38, or between 20 and 35, or between 25 and 35, where MIF is the melt flow index at 190°C under a load of 21.60 kg and MIP is the melt flow index at 190°C under a load of 5 kg, both measured according to ISO 1133-2:2011; 3) MIF of 6-15g / 10min or 6-13g / 10min, especially 6.5-15g / 10min or 6.5-13g / 10min; 4) HMWcopo index of 0.5 to 3.5, preferably 0.5 to 3.3, more preferably 0.8 to 3.3 or 0.5 to 3.0, more preferably 0.8 to 3.3 or 0.8 to 3.0; 5) A long-chain branching index (LCBI) of 0.82 or less, or 0.80 or less, or 0.72 or less, in particular 0.82-0.45, or 0.80-0.45, or 0.72-0.45; The HMWcopo index is determined according to the following formula: HMWcopo = (η0.02 xt maxDSC ) / (10^5) In the above formula, η 0.02 is the complex viscosity (Pa.s) of the melt measured at a temperature of 190°C on a parallel plate rheometer in dynamic oscillatory shear mode with an applied angular frequency of 0.02 rad / s; maxDSC is the time (in minutes) required to reach the maximum value of the heat flow of crystallization at a temperature of 124° C. under quiescent conditions measured in isothermal mode in a differential scanning calorimetry apparatus; LCBI is the measured mean square radius of gyration R measured by GPC-MALLS at a molecular weight of 1,000,000 g / mol. g vs. the mean square radius of gyration for linear PE of the same molecular weight; 6) η 0.02 is 150,000 or less, preferably 130,000 or less, more preferably 125,000 or less, the lower limit being 40,000 in all cases, more preferably 50,000 in all cases.

[0008] From the above-defined characteristics 2) and 3), it can be seen that the MIP value for the present polyethylene composition is in the range of about 0.15 to about 0.75 g / 10 min. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows a diagram of a cascade of a fluidized bed reactor and a multi-zone circulating reactor having two interconnected reaction zones.

[0010] The drawings are exemplary embodiments of a simplified flow chart of the steps for producing various embodiments of the polyethylene compositions disclosed herein in two series-connected gas phase reactors suitable for use with various embodiments of the ethylene polymerization process disclosed herein.

[0011] It should be understood that the various embodiments are not limited to the arrangements and instrumentality shown in the drawings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The expression "polyethylene composition" preferably includes compositions made up of two or more ethylene polymer components having different molecular weights, and such compositions are also referred to in the art as "bimodal" or "multimodal" polymers.

[0013] Generally, the polyethylene compositions of the present invention comprise one or more ethylene copolymers.

[0014] All the characteristics defined in this specification, including the above-defined characteristics 1) to 6), refer to the ethylene polymer composition. One or more of the characteristics can be modified by adding other components, such as additives, which are commonly applied in the art.

[0015] In particular, the polyethylene composition may be reacted with a radical initiator in order to modify the rheological and structural characteristics, such as the melt index value, within or outside a previously given interval.

[0016] The radical initiator is preferably selected from organic peroxides.

[0017] Particularly useful organic peroxides are organic monoperoxides and / or organic diperoxides. Such organic monoperoxides and diperoxides may have a half-life of 1 hour at a temperature in the range of about 125° C. to about 145° C., alternatively in the range of about 130° C. to about 140° C., alternatively in the range of about 132° C. to about 136° C. Further alternatives include organic peroxides having a half-life of 0.1 hours at a temperature in the range of about 145° C. to 165° C., or in the range of about 150° C. to about 160° C., or in the range of about 154° C. to 158° C. The organic peroxides may have a molecular weight in the range of about 175 g / mol to about 375 g / mol, alternatively in the range of about 200 g / mol to about 350 g / mol. Mixtures of two or more peroxides may be used if desired. Suitable organic peroxides include, but are not limited to, dicumyl peroxide (CAS® Registry No. 80-43-3), di(tert-butylperoxyisopropyl)benzene(et al.) (CAS® Registry No. 25155-25-3), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (CAS® Registry No. 78-63-7), tert-butylcumyl peroxide (CAS® Registry No. 3457-61-2), and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne (CAS® Registry No. 1068-27-5), and mixtures thereof.

[0018] A preferred organic peroxide is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0019] The reaction with the radical initiator may be carried out by any means under conditions known in the art to be effective for radical-initiated reactions with olefin polymers.

[0020] In particular, it is known that such reactions can be carried out in conventional equipment commonly used for processing polymers in the molten state, such as, in particular, twin-screw extruders, operating under an inert atmosphere, e.g. under nitrogen.

[0021] The amount of radical initiator to be added to the polyethylene composition can be easily determined by one skilled in the art. Generally, such amount is comprised in the range of 0.1 to 100 ppm by weight, in particular 0.5 to 100 ppm by weight, of peroxide to the polyethylene composition, the exact amount being determined by the desired change in rheology, e.g., ER, or by film testing, e.g., bubble stability testing.

[0022] The reaction temperature is preferably in the range of 180 to 300°C.

[0023] The MIF / MIP ratio provides a rheological measure of the molecular weight distribution.

[0024] Another measure of molecular weight distribution is M w / M n is given by the ratio, where M w is the weight average molar mass, M n is the number average molar mass, both measured by GPC (gel permeation chromatography) as explained in the examples.

[0025] M of the polyethylene composition of the present invention w / M n The value is preferably in the range of 25-65, preferably 30-65.

[0026] The Mw value is preferably 200,000 to 400,000 g / mol.

[0027] Additional information regarding the molecular weight distribution is provided by the rheological polydispersity, ER, which is determined from a plot of storage modulus (G') versus loss modulus (G") and is a measure of the high molecular weight end polydispersity. It is calculated by the following formula: ER=(1.781*10 -3 )*G' G''=5,000 dyn / cm 2 With the value of .

[0028] The preferred ER value for the polyethylene composition of the present invention is 2-5.

[0029] Furthermore, it is preferred that the polyethylene composition of the present invention has at least one of the following additional characteristics: - The density of the ethylene homopolymer or copolymer A) is 0.960 to 0.971 g / cm 3 , more preferably 0.965 to 0.970 g / cm 3 ; - Eta divided by 1000 0.02 and the LCBI, the ratio (η 0.02 / 1000) / LCBI is 120 to 180, preferably 125 to 178; - a comonomer content of less than or equal to 2% by weight, in particular from 0.2 to 2% by weight, based on the total weight of the composition (as determined by IR); - ET value below 25, especially 3-25; ET is calculated according to the following formula: ET at tan δ=C3=C2 / G* where: G*=[(G') 2 +(G'') 2 ] 1 / 2 ; tan δ=G′′ / G′; C2=10 6 dyn / cm 2 and C3=1.5 G' = storage modulus; G' = loss modulus; Both G' and G" are measured by dynamic oscillatory shear in a plate-plate rotational rheometer at a temperature of 190°C; - Long-chain branching index (LCBI) is 0.70 or less, in particular, 0.70 to 0.45.

[0030] In order to achieve the best processability in terms of extrusion pressure, the value of MIF should preferably be in the range of 9-15 g / 10 min, or 9-13 g / 10 min.

[0031] The comonomer or comonomers present in the ethylene copolymers are generally selected from olefins having the formula CH2=CHR, where R is a linear or branched alkyl radical having from 1 to 10 carbon atoms.

[0032] Specific examples are propylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, octene-1 and decene-1. A particularly preferred comonomer is hexene-1.

[0033] As mentioned above, the polyethylene composition may be particularly well processed by the film blowing process.

[0034] Indeed, the polyethylene compositions provide breathable films with high bubble stability ratings while retaining excellent DDI values.

[0035] A blown film of the polyethylene composition may have a bubble stability score of greater than 40 for a film thickness of 12.5 μm and a DDI of greater than 200 g, preferably greater than 350 g.

[0036] Generally, the balance of the above properties is such that when the DDI value is 200 to 350 g, the bubble stability score (called the simplicity BSS) is 52 or more, particularly 52 to 80, while when the DDI value is 350 g or more, the BSS score is 40 or more, particularly 40 to less than 80.

[0037] Blown film (also called tubular film) extrusion technology is well known for the production of thin plastic films. The process involves the extrusion of molten thermoplastic resin through an annular die followed by a "bubble-like" expansion of the molten web.

[0038] The polyethylene composition ensures high film bubble stability even under process conditions typical of large industrial plants, i.e. the film bubble emerging from the annular die remains stable even at high take-off speeds and shows no tendency to change shape in both the axial or radial direction.

[0039] Preferably, the bubble has a frost line that delimits the molten material from the frozen material that oscillates axially no more than ±3 cm during the bubble stability test (performed as detailed in the Examples) at maximum withdrawal speed.

[0040] The present disclosure further relates to a breathable film comprising the polyethylene composition as described above. In particular, the breathable film may be monolayer or multilayer, wherein at least one layer comprises the polyethylene composition.

[0041] The breathable film may have a thickness in the range of 5 to 200 μm, preferably 10 to 100 μm.

[0042] Although there is in principle no restriction on the type of polymerization process and catalyst used, it has been found that the polyethylene composition of the present invention can be produced by a gas phase polymerization process in the presence of a Ziegler-Natta catalyst.

[0043] Ziegler-Natta catalysts include the reaction product of an organometallic compound of Groups 1, 2 or 13 of the Periodic Table of the Elements with a transition metal compound (according to the new notation) of Groups 4 to 10 of the Periodic Table of the Elements. In particular, the transition metal compound may be selected from compounds of Ti, V, Zr, Cr and Hf, preferably supported on MgCl2.

[0044] Particularly preferred catalysts include the reaction product of said organometallic compounds of Groups 1, 2 or 13 of the Periodic Table of the Elements and a solid catalyst component comprising a Ti compound supported on MgCl2.

[0045] The preferred organometallic compounds are organoaluminum compounds.

[0046] Accordingly, in a preferred embodiment, the polyethylene composition of the present invention is obtained by using a Ziegler-Natta polymerization catalyst, more preferably a Ziegler-Natta catalyst supported on MgCl2, even more preferably a Ziegler-Natta catalyst comprising the reaction product of the following a) to c) a) a solid catalyst component optionally comprising a Ti compound supported on MgCl2 and an electron donor compound ED; b) organoaluminum compounds; and optionally c) External electron donor compound ED ext .

[0047] Suitable titanium compounds are tetrahalides or compounds of the formula TiX n (OR 1 ) 4-n where 0≦n≦3, X is a halogen, preferably chlorine, and R 1 is C1-C 10 It is a hydrocarbon group. Titanium tetrachloride is the preferred compound.

[0048] The ED compound is generally selected from alcohols, ketones, amines, amides, nitriles, alkoxysilanes, aliphatic ethers, and esters of aliphatic carboxylic acids.

[0049] Preferably the ED compound is selected from amides, esters and alkoxysilanes.

[0050] Esters are particularly preferred as ED compounds, because excellent results can be obtained using esters.Specific examples of esters are alkyl esters of C1-C20 aliphatic carboxylic acids, particularly C1-C8 alkyl esters of aliphatic monocarboxylic acids, such as ethyl acetate, methyl formate, ethyl formate, methyl acetate, propyl acetate, i-propyl acetate, n-butyl acetate, i-butyl acetate.Furthermore, aliphatic ethers are preferred, particularly C2-C20 aliphatic ethers, such as tetrahydrofuran (THF) or dioxane.

[0051] In said solid catalyst components, MgCl2 is the basic support, even if additional supports are used in minimal amounts. MgCl2 can be used as such or obtained from Mg compounds used as precursors that can be converted to MgCl2 by reaction with halogenated compounds. The use of activated MgCl2, which is widely known from the patent literature as a support for Ziegler-Natta catalysts, is particularly preferred. US Patent Nos. 4,298,718 and 4,495,338 were the first to describe the use of these compounds in Ziegler-Natta catalysis. From these patents it is known that activated magnesium dihalides used as supports or co-supports in catalyst components for olefin polymerization are characterized by X-ray spectra in which the most intense diffraction lines, which are represented in the reference ASTM card of the spectrum of the non-activated halide, are broadened with decreasing intensity. In the X-ray spectrum of the preferred magnesium dihalides in activated form, the most intense lines are replaced by halos that decrease in intensity and are displaced to lower angles compared to the lines with the most intense maximum intensity.

[0052] Particularly suitable for the preparation of the polyethylene composition of the present invention are catalysts which are prepared by first contacting a titanium compound with MgCl or a precursor Mg compound, optionally in the presence of an inert medium, to produce a solid component a) containing the titanium compound supported on MgCl, and optionally contacting component a) with an ED compound, optionally in the presence of an inert medium, which is added to the reaction mixture alone or in a mixture with other compounds in which the ED compound is predominant.

[0053] By the term "major component," we mean that the ED compound is the major component in terms of molar amount relative to other possible mixtures, excluding the inert solvent or diluent used in handling the contact mixture. The ED treated product can then be washed with a suitable solvent to recover the final product. If necessary, the treatment with the preferred ED compound can be repeated one or more times.

[0054] As mentioned above, precursors of MgCl2 can be used as the starting requisite Mg compound. This can be selected, for example, from Mg compounds of formula MgR'2, where the R' groups can be independently an optionally substituted C1-C20 hydrocarbon group, an OR group, an OCOR group, or chlorine, where R is an optionally substituted C1-C20 hydrocarbon group, with the proviso that the R' group is not also chlorine. Also suitable as precursors are Lewis adducts between MgCl2 and a suitable Lewis base. A particularly preferred class is MgCl2(R"OH) m The emulsion is constituted by an adduct, in which the R" group is a C1-C20 hydrocarbon group, preferably a C1-C10 alkyl group, and m is 0.1-6, preferably 0.5-3, more preferably 0.5-2. Such types of adducts are generally obtained by mixing an alcohol with MgCl2 in the presence of an inert hydrocarbon immiscible with the adduct, and operating under stirring conditions at the melting point of the adduct (100-130°C). The emulsion is then rapidly quenched, thereby causing the adduct to solidify in the form of spherical particles. Representative methods for producing these spherical adducts are reported, for example, in U.S. Pat. Nos. 4,469,648, 4,399,054 and WO 98 / 44009. Other methods that can be used for spheronization include the spray cooling method described, for example, in U.S. Pat. Nos. 5,100,849 and 4,829,034.

[0055] MgCl2·(EtOH) m Of particular interest are adducts, where m is between 0.15 and 1.7, which are obtained by subjecting the adducts with higher alcohol contents to a thermal dealcoholization process carried out in a nitrogen stream at temperatures comprised between 50 and 150° C. until the alcohol content is reduced to the abovementioned values. A process of this type is described in EP 395083.

[0056] Alternatively, dealcoholation can be accomplished chemically by contacting the adduct with a compound capable of reacting with the alcohol group.

[0057] In general, these dealcoholated adducts also have a porosity (measured by the mercury method) of 0.15 to 2.5 cm2, with pores of less than 0.1 μm in radius. 3 / g, preferably 0.25 to 1.5 cm 3 / g.

[0058] These adducts are preferably titanium tetrachloride, TiX as mentioned above. n (OR 1 ) 4-n The adduct is reacted with a titanium compound (or a mixture thereof). The reaction with the Ti compound can be carried out by suspending the adduct in TiCl4 (generally cooled). The mixture is heated to a temperature in the range of 80-150°C and held at that temperature for 0.5-2 hours. The treatment with the titanium compound can be carried out one or more times. It may also be carried out in the presence of an electron donor compound as described above. At the end of the process, the solid is recovered by separation of the suspension through conventional methods (e.g. settling and removal of the liquid, filtration, centrifugation) and may be washed with a solvent. Washing is generally carried out with an inert hydrocarbon solution, although it is also possible to use more polar solvents (e.g. solvents with a higher dielectric constant), such as halogenated hydrocarbons, etc.

[0059] The solid component a) can then be contacted with the ED compound under conditions that allow an effective amount of the donor to be immobilized on the solid, as described above. Due to the high versatility of the method, the amount of donor used can vary widely. By way of example, the donor can be used in a molar ratio ranging from 0.5 to 20, preferably from 1 to 10, relative to the Ti content in the intermediate product. Although not strictly required, the contacting is generally carried out in a liquid medium, such as a liquid hydrocarbon. The temperature at which the contacting is carried out can vary depending on the nature of the reagents. Generally, the temperature is comprised in the range of -10 to 150°C, preferably from 0 to 120°C. Temperatures that cause decomposition or degradation of any particular reagent should generally be avoided, even if this temperature is generally within a suitable range. The treatment time can also vary depending on other conditions, such as the nature of the reagents, the temperature, the concentration, etc. Generally, this contacting step can last from 10 minutes to 10 hours, more frequently from 0.5 to 5 hours. If necessary, this step can be repeated one or more times to further increase the final donor content. At the end of this step, the solids may be recovered by separation of the suspension through conventional methods (e.g., settling and removal of the liquid, filtration, centrifugation) and washed with a solvent. Washing is usually carried out with an inert hydrocarbon liquid, although more polar solvents (e.g., having a higher dielectric constant) such as halogenated or oxygenated hydrocarbons can also be used.

[0060] As mentioned above, the solid catalyst component is converted into a catalyst for the polymerization of olefins by reacting it with an organometallic compound of Group 1, 2 or 13 of the Periodic Table of the Elements, in particular an Al-alkyl compound, by known methods.

[0061] The alkyl-Al compound is preferably selected from trialkylaluminum compounds such as triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, etc. It is also possible to use alkylaluminum halides, alkylaluminum hydrides or alkylaluminum sesquichlorides, such as AlEt2Cl and A12Et3Cl3, alternatively in mixture with said trialkylaluminum compounds.

[0062] External electron donor compound ED optionally used in the preparation of said Ziegler-Natta catalyst ext may be the same or different from ED used in the solid catalyst component a). It is preferably selected from the group consisting of ethers, esters, amines, ketones, nitriles, silanes and mixtures thereof. It can be particularly advantageously selected from C2-C20 aliphatic ethers, in particular cyclic ethers, preferably cyclic ethers having 3 to 5 carbon atoms, such as tetrahydrofuran and dioxane.

[0063] The catalyst component a) can preferably be prepolymerized by producing small amounts of a polyolefin, preferably polypropylene or polyethylene, according to known techniques.

[0064] When the solid component a) is treated with an ED compound, there is the possibility of carrying out a prepolymerization before or after such treatment.

[0065] The amount of prepolymer produced can be up to 500 g per gram of component a), preferably between 0.5 and 20 g per gram of solid component a).

[0066] The prepolymerization is carried out using a suitable cocatalyst such as an organoaluminum compound which may be used in combination with an external electron donor compound as described above.

[0067] This can be carried out in the liquid or gas phase at a temperature of 0 to 80°C, preferably 5 to 70°C.

[0068] It has now been found that by using the aforementioned polymerization catalysts the polyethylene composition of the present invention may be prepared by a process comprising the following steps, in any mutual order: a) polymerizing ethylene, optionally with one or more comonomers, in a gas phase reactor in the presence of hydrogen; b) copolymerizing ethylene with one or more comonomers in a separate gas phase reactor in the presence of a lesser amount of hydrogen than in step a); Here, in at least one of the gas-phase reactors, the growing polymer particles flow upwards under fast fluidization or transport conditions through a first polymerization zone (riser), after leaving the riser they enter a second polymerization zone (downcomer), through which they flow downwards under the action of gravity, after leaving the downcomer they are again introduced into the riser, thereby establishing a polymer circulation between the two polymerization zones.

[0069] In the first polymerization zone (riser), fast flow conditions are established by feeding a gas mixture containing one or more olefins (ethylene and comonomers) at a velocity higher than the transport velocity of the polymer particles. The velocity of said reaction gas mixture is preferably between 0.5 and 15 m / s, more preferably between 0.8 and 5 m / s. The terms "conveying velocity" and "fast flow conditions" are well known in the art, for their definitions see, for example, D. Geldart, Gas Fluidisation Technology, page 155 et seq., J. Wiley & Sons Ltd., 1986.

[0070] In the second polymerization zone (downcomer), the polymer particles flow under the action of gravity in a densified form, so that the density of the solids reaches a high value (mass of polymer per volume of reactor), which is close to the bulk density of the polymer.

[0071] In other words, the polymer flows vertically downward through the downcomer in plug flow (packed flow mode) so that only small amounts of gas are entrained between the polymer particles.

[0072] By such a process it is possible to obtain from step a) a component A), as defined previously, which is an ethylene polymer having a lower molecular weight than the ethylene copolymer component B) obtained from step b).

[0073] Preferably, the polymerization of ethylene (step a) to produce ethylene polymers of relatively low molecular weight is carried out upstream of the copolymerization of ethylene (step b) to produce ethylene copolymers of relatively high molecular weight. To this end, the gas mixture comprising ethylene, hydrogen, optionally comonomers and an inert gas from step a) is fed to a first gas-phase reactor, preferably a gas-phase fluidized bed reactor. The polymerization is carried out in the presence of the Ziegler-Natta catalyst described above.

[0074] The amount of hydrogen fed varies depending on the availability of a particular catalyst, but in any case it is suitable that the melt flow index MIE of the ethylene polymer obtained in step a) is less than or equal to 130 g / 10 min. To obtain an MIE in the above range, the hydrogen / ethylene molar ratio in step a) is 1-4 in the direct process and the amount of ethylene monomer is 2-20% by volume, preferably 4-15% by volume, based on the total volume of gas present in the polymerization reactor. The remaining part of the feed mixture is made up of an inert gas and one or more comonomers, if present. The inert gas necessary to dissipate the heat generated by the polymerization reaction is conveniently selected from nitrogen or saturated hydrocarbons, the most preferred being propane.

[0075] In step a), the operating temperature in the reactor is selected in the range of 50-120° C., preferably in the range of 65-100° C., and the operating pressure is 0.5-10 MPa, preferably 2.0-5 MPa.

[0076] The ethylene polymer obtained in step a) accounts for 30-70% of the total weight of the ethylene polymer produced in the whole process, i.e. in the first and second reactors connected in series.

[0077] The ethylene polymer and entrained gas from step a) are then subjected to a solid / gas separation step to prevent the gas mixture from the first polymerization reactor from being introduced into the reactor of step b) (the second gas phase polymerization reactor). The gas mixture is recycled to the first polymerization reactor, and the separated ethylene polymer is fed to the reactor of step b). A suitable feed point for introducing the polymer into the second reactor is located at the junction of the downcomer and the upcomer, where the solid concentration is particularly low, so that it does not adversely affect the flow conditions.

[0078] The operating temperature of step b) is in the range of 65-95°C, and the pressure is in the range of 1.5-4.0 MPa. The second gas phase reactor is intended to copolymerize ethylene with one or more comonomers to produce a relatively high molecular weight ethylene copolymer. Furthermore, the reactor of step b) can be conveniently operated by establishing different conditions of monomer and hydrogen concentration in the riser and downcomer to broaden the molecular weight distribution of the final ethylene polymer.

[0079] For the above purpose, in step b) the polymer particles are entrained and the gas mixture leaving the riser is partially or totally prevented from entering the downcomer, so that two different gas composition zones are obtained. This can be achieved by feeding a gas and / or liquid mixture into the downcomer through a line located at a suitable point of the downcomer, preferably at its upper part. Said gas and / or liquid mixture should have a suitable composition different from the gas mixture present in the upcomer. Said gas and / or liquid mixture can be adjusted so that an upward flow of gas countercurrent to the flow of the polymer particles occurs, especially at its upper part, acting as a barrier for the gas mixture entrained with the polymer particles coming from the riser. In particular, it is advantageous to feed a mixture with a low hydrogen content to produce a fraction of high molecular weight polymer in the downcomer. One or more comonomers may be fed to the downcomer in step b), optionally together with ethylene, propane or other inert gases.

[0080] In the direct process, the hydrogen / ethylene molar ratio in the downcomer in step b) ranges from 0.01 to 0.5, and the ethylene concentration in the direct process is 5 to 20% by volume, based on the total volume of gas present in the downcomer. The remainder is propane or a similar inert gas. Because the molar concentration of hydrogen present in the downcomer is very low, carrying out the process of the invention makes it possible to combine relatively large amounts of comonomer with the high molecular weight polyethylene fraction.

[0081] The polymer particles leaving the downcomer are reintroduced into the riser in step b).

[0082] In the riser of step b), the hydrogen / ethylene molar ratio is in the range of 0.01-0.5 and the ethylene concentration is in the range of 5-20% by volume based on the total volume of gas present in the riser.

[0083] The content of the comonomer is adjusted so that the density of the final polyethylene is the desired value. The concentration of the comonomer in the riser and the downcomer is 0.05 to 1% by volume based on the total volume of the gas present in the riser.

[0084] The remainder is propane or other inert gas.

[0085] Further details regarding the above mentioned polymerization methods are provided in WO2005019280.

[0086] Working Example The practice and advantages of the various embodiments, compositions and methods as provided herein are illustrated in the following examples, which are merely illustrative and are not intended to limit the scope of the appended claims in any way.

[0087] The following analytical methods are used to characterize the polymer compositions.

[0088] density Measured at 23°C according to ISO1183-1:2012.

[0089] Composite shear viscosity η 0.02 (eta(0.02))ER and ET Measurements were performed at an angular frequency of 0.02 rad / s and 190° C. as described below.

[0090] The specimens were melt-compressed into 1 mm thick plates under 200 °C and 200 bar for 4 min. Disk specimens with a diameter of 25 mm were stamped and inserted into the rheometer preheated at 190 °C. The measurements can be performed with any commercially available rotational rheometer. Here, an Anton Paar MCR 300 equipped with plate-plate geometry was used. A so-called frequency-sweep was performed at T = 190 °C under a constant strain amplitude of 5% (after annealing the specimens at the measurement temperature for 4 min) to measure and analyze the stress response of the material in the range of excitation frequencies ω from 628 to 0.02 rad / s. A standardized base software was used to calculate the rheological properties, i.e. storage modulus G′, loss modulus G″, phase lag δ (=arctan(G″ / G′)) and complex viscosity η* as a function of the applied frequency, i.e. η*(ω) = [G′(ω) 2+G″(ω) 2 ] 1 / 2 / ω. The latter value at an applied frequency ω of 0.02 rad / s is η 0.02 It is.

[0091] ER was determined by the method described in the literature [R. Shroff and H. Mavridis, "New Measures of Polydispersity from Rheological Data on Polymer Melts," J. Applied Polymer Science 57 (1995) 1605 (see also U.S. Pat. No. 5,534,472, column 10, lines 20-30)]. It is calculated by the following formula: ER=(1.781*10 -3 )*G' G''=5,000 dyn / cm 2 With the value of .

[0092] As those skilled in the art will recognize, a minimum G" value of 5,000 dyn / cm 2 Above this threshold, the determination of ER involves extrapolation. The calculated ER value will then vary depending on the degree of nonlinearity in the log G' vs. log G" plot. The temperature, plate diameter, and frequency ranges are chosen to ensure that the minimum G" value is within the resolution of the rheometer and is below 5,000 dyn / cm. 2 is chosen to be close to or less than

[0093] Similarly, ET was determined by the method of the literature [R. Shroff and H. Mavridis, "New Measures of Polydispersity from Rheological Data on Polymer Melts," J. Applied Polymer Science 57 (1995) 1605-1626]. ET is a sensitive constant for describing the polydispersity at the very high molecular weight end of a polymer and / or describing a very broad molecular weight distribution. The higher the ET, the broader the polymer resin is rheologically.

[0094] This is calculated according to the following formula: ET at tan δ=C3=C2 / G* where: G*=[(G') 2 +(G'') 2 ] 1 / 2 ; tan δ=G′′ / G′;

[0095] HMWcopo index To quantify the crystallization and processability potential of a polymer, the HMWcopo (High Molecular Weight Copolymer) index is used and is defined by the following formula: HMWcopo = (η 0.02 xt maxDSC ) / (10^5)

[0096] This exponent decreases as the easy processing (low melt viscosity) and rapid crystallization potential of the polymer increases. It also correlates with the melt complex shear viscosity (η 0.02 ) and the amount of high molecular weight fraction associated with quiescent crystallization (t maxDSC ) is a description and quantitative method for the incorporation of comonomers that retard crystallization.

[0097] t maxDSC is measured under isothermal conditions at a constant temperature of 124 °C using a differential scanning calorimeter (TA Instruments Q2000). 5-6 mg of sample is weighed and transferred into aluminum DSC pans. The sample is heated at 20 K / min up to 200 °C to remove the thermal history and cooled at 20 K / min to the test temperature. Immediately after cooling, the isothermal test is started immediately and the time until crystallization occurs is recorded. The crystallization heat flow maximum (peak), t maxDSC The time interval from t to t is measured using the supplier's software (TA Instruments). The measurement is repeated three times and the average value (in minutes) is calculated. If no crystallization is observed under these conditions for more than 120 minutes, t maxDSCThe value of =120 min is used for further calculation of the HMWcopo index.

[0098] Melt Viscosity η 0.02 Value to t maxDSC Multiply the values ​​and normalize the resulting value by a factor of 100000 (10^5).

[0099] Molecular weight distribution measurement The determination of the molar mass distribution and the resulting average Mn, Mw and Mw / Mn were carried out by high temperature gel permeation chromatography using the method described in ISO 16014-1, -2, -4, published in 2003. The description according to the mentioned ISO standard is as follows: solvent 1,2,4-trichlorobenzene (TCB), temperature of the apparatus and solution 135°C and a PolymerChar (Valencia, Paterna 46980, Spain) IR-4 infrared detector usable with TCB as concentration detector, a WATERS Alliance 2000 equipped with the following pre-column SHODEX UT-G and separation columns SHODEX UT 806 M (3x) and SHODEX UT 807 (Showa Denko Europe GmbH, Konrad-Zuse-Platz 4, 81829 Muenchen, Germany) connected in series were used.

[0100] Solvents were vacuum distilled under nitrogen and stabilized with 0.025 wt% 2,6-di-tert-butyl-4-methylphenol. The flow rate used was 1 ml / min, the injection volume was 500 μl, and the polymer concentrations were in the range of 0.01% < concentration < 0.05% (w / w). Molecular weight calibration was performed using monodisperse polystyrene (PS) standards from Polymer Laboratories (now Agilent Technologies, Herrenberger Str. 130, 71034 Boeblingen, Germany) in the range of 580 g / mol to 11.6 million g / mol, additionally with hexadecane.

[0101] The calibration curve was then fitted to polyethylene (PE) by the Universal Calibration method (Benoit H., Rempp P. and Grubisic Z., & in J. Polymer Sci., Phys. Ed., 5, 753(1967)). Thus, the Mark-Houwink parameters used were: for PS, k PS = 0.000121 dl / g, α PS = 0.706, and for PE, k PE = 0.000406 dl / g, α PE = 0.725, valid in TCB at 135° C. Data recording, calibration and calculations were performed using NTGPC_Control_V6.02.03 and NTGPC_V6.4.24, respectively (hs GmbH, Hauptstrasse 36, D-55437 Ober-Hilbersheim, Germany).

[0102] Melt Flow Index Measured according to ISO 1133-2:2011 at 190°C under specified load.

[0103] Long Chain Branching Index (LCBI) The LCB index is 10 6This corresponds to the branching factor g' measured relative to the molecular weight in g / mol. The branching factor g', which allows the determination of long chain branching at high Mw, was measured by gel permeation chromatography (GPC) coupled with multi-angle laser light scattering (MALLS). The radius of gyration for each fraction eluted from the GPC (as described above, but with a flow rate of 0.6 ml / min and a column packed with 30 μm particles) is measured by analyzing the light scattering from different angles using MALLS (detector Wyatt Dawn EOS, Wyatt Technology, Santa Barbara, CA). A laser source of 120 mW with a wavelength of 658 nm was used. A specific index of refraction of 0.104 ml / g was obtained. Data evaluation was carried out with Wyatt ASTRA 4.7.3 and CORONA 1.4 software. The LCB index is measured as described below.

[0104] The parameter g' is the ratio of the measured mean square radius of gyration to the measured mean square radius of gyration of a linear polymer of the same molecular weight. Linear molecules exhibit a g' of 1, whereas in the presence of LCB they exhibit values ​​less than 1. The value of g' as a function of molecular weight M was calculated from the following equation: g′(M)= <Rg 2 > サンプル、M / <Rg 2 > 線形参照、M Where: <Rg 2 >, M is the mean square root radius of gyration for the fraction of molecular weight M.

[0105] The radius of gyration for each fraction eluted from the GPC (as described above, but using a flow rate of 0.6 ml / min and a column packed with 30 μm particles) is measured by analyzing light scattering from various angles. Thus, the molecular weight M and <Rg 2 > サンプル、M Measure M=10 6 It is possible to define g' in terms of g / mol. <Rg 2 > 線形参照、Mis calculated according to the established relationship between radius of gyration and molecular weight for linear polymers in solution (ref. [Zimm BH, Stockmayer WH, "The Dimensions of Chain Molecules Containing Branches and Rings", The Journal of Chemical Physics 17, 1301 (1949)]) and confirmed by measuring a linear PE reference using the same equipment and methodology described.

[0106] For experimental validation, two linear PE references, IUPAC 5A and IUPAC 5B, were used.

[0107] Comonomer Content The comonomer content was measured by IR according to ASTM D 6248 98 using a Bruker FT-IR spectrophotometer Tensor27 and calibrated using a chemometric model to measure ethyl- or butyl-side chains in PE for butene or hexene as comonomer, respectively. The results were compared and found to be in agreement with the predicted comonomer content derived from the mass-balance of the polymerization process.

[0108] Dart Drop Index (DDI) The thickness of the film was 12.5 μm and was measured according to ASTM D1709, method A. The films were produced as described in the following bubble stability test, according to which the basic settings were as follows: -Throughput: 72Kg / h; -Blow-up ratio BUR:4; -Neck length NL: 960mm (8DD); -Haul-off speed: 67m / min.

[0109] Bubble Stability Test and Extrusion Pressure The Bubble Stability Test (BST) is performed on a series of Hosokawa-Alpine conventional monolayer blown films having the following properties: - a single screw extruder with a grooved and cooled feed section, with gravimetric dosing; - a screw with diameter D=50 mm and length 30D, equipped with shear and mixing elements; Temperature profile (11 zones) ramping from 180°C to 220°C to achieve melt temperatures in the range of -205°C + / - 5°C (Extruder: 180 / 185 / 190 / 195 / 200 / 205 / 205, Head: 210 / 210 / 220 / 220); - Melt temperature measured after the screen; -Screen exchanger: Screen area 120cm 2 No screen pack is used, just a die plate with 50-60 holes, each about 2mm in diameter; - Melt pressure (extrusion pressure): measured before the screen changer; - A film die with a diameter of 120 mm, a die gap of 1.0 mm and a spiral mandrel (4 ports); -Double lip cooling ring (Hosokawa-Alpine CR32), chilled cooling air (18℃+ / -2℃), no internal bubble cooling IBC; - Compensation basket; basket height is adjusted to match neck length (use 970mm from the top cooling ring to the bottom basket) -Wood flattening device, take-out unit and film winder;

[0110] The bubble stability test begins with the following basic settings: -Throughput: 72Kg / h; -Blow-up ratio BUR:4; -Neck length NL: 960mm (8DD); -Film thickness: 12.5μm; -Haul-off speed: 67m / min.

[0111] The horizontal (HM) and vertical movement (VM) of the bubble are observed for 3 min under stable conditions.

[0112] If the bubble movement is less than + / - 3cm in either direction the sample is given a score of 25 points.

[0113] A cross-line laser is used to measure the horizontal and vertical movement of the bubble (see diagram below).

[0114] Subsequent stepwise increase in take-off speed to 5 m / min (holding throughput, BUR and NL constant) results in a decrease in film thickness as shown in the table below.

[0115] At a given withdrawal speed, the bubbles are observed again for 3 minutes after stable conditions are reached.

[0116] HM and V.M. If it is ≦+ / -3cm, 3 points will be added; If it is ≦+ / -5cm, 2 points will be added; If it is ≦+ / -10cm, 1 point will be added; If ≧+ / -10cm, 0 points will be added.

[0117] If the displacement is ≦5 cm (2 or 3 points), the test continues and the take-off speed may be further increased. If the displacement is ≧+ / - 5 cm (1 or 0 points), the test is terminated.

[0118] The test will start with the basic settings (72Kg / h, BUR:4, NL960mm, 12.5μm, 67m / min) and if HM or VM is >3cm, reduce the score of 25 by 3 points (HM or VM >+ / -10cm), 2 points (HM or VM + / -5~10cm), or 1 point (HM or VM + / -3~5cm), making the minimum score 22 points.

[0119] [ka]

[0120] The examples below show results for samples where the test was completed with a take-off speed of 97 m / min and horizontal or vertical displacement of the bubble of >5 cm and ≦10 cm (1 point, end of test).

[0121] In this example the total score is 39 points.

[0122] [Table 1]

[0123] -Process Settings The polymerization process was carried out under continuous conditions in a plant containing two gas phase reactors connected in series as shown in FIG.

[0124] The polymerization catalyst is prepared as follows.

[0125] Following the method described in Example 2 of US Pat. No. 4,399,054, but operating at 2000 RPM instead of 10,000 RPM, an adduct of magnesium chloride and alcohol containing about 3 moles of alcohol was prepared. The adduct was subjected to heat treatment under nitrogen flow over a temperature range of 50-150°C until a weight content of 25% alcohol was reached. 1 L of TiCl4 was introduced at about 0°C into a 2 L 4-neck round bottom flask purged with nitrogen. Then, 70 g of spherical MgCl2 / EtOH adduct containing 25% by weight of ethanol prepared as above at about the same temperature was added under stirring. The temperature was increased to about 140°C in about 2 hours and held for about 60 minutes. Then, the stirring was stopped, the solid product was allowed to settle and the supernatant liquid was siphoned off.

[0126] The solid residue was then washed once with heptane at 80°C, five times with hexane at 25°C, and dried under vacuum at 30°C.

[0127] A sufficient amount of the solid catalyst component, prepared according to the above reported synthetic route, was prepolymerized with propylene in an amount of 1 g polypropylene / g catalyst component, according to the method described in Example 7 of WO01 / 85803.

[0128] polymerization Example 1 Polyethylene was produced in a cascade of a fluidized bed reactor and a multi-zone circulating reactor having two interconnected reaction zones as shown in FIG.

[0129] To carry out the polymerization, 9.5 g / h of the solid catalyst prepared as described above were fed using 1.5 kg / h of liquid propane to a first stirred precontact vessel, which was also charged with triisobutylaluminum (TIBA). The weight ratio of aluminum alkyl to Ziegler catalyst was 2:1. The first precontact vessel was maintained at 40° C. with an average residence time of 25 minutes. The catalyst suspension of the first precontact vessel was continuously transferred to a second stirred precontact vessel, which was operated with an average residence time of 25 minutes and was also maintained at 40° C. The catalyst suspension was continuously transferred via line (2) to a fluidized bed reactor (FBR) (1).

[0130] Ethylene was polymerized in the presence of propane as inert diluent in a fluidized bed reactor (1) using hydrogen as molecular weight regulator. 47 kg / h ethylene, 165 g / h hydrogen and 11 kg / h propane were fed to the fluidized bed reactor (1) via line (3). No comonomer was added. The polymerization was carried out at a polymerization temperature of 80° C. and a pressure of 3.0 MPa. The selected feed rates resulted in an ethylene concentration of 7.4% by volume in the reactor and a hydrogen / ethylene molar ratio of 2.7 in the reactor.

[0131] The polyethylene obtained in the fluidized bed reactor (1) had an MIE of 102 g / 10 min and a viscosity of 0.968 g / cm 3 The density was 1.01 μm.

[0132] The polyethylene obtained in the fluidized bed reactor (1) was continuously transferred to a multi-zone circulation reactor (MZCR), which was operated at a pressure of 2.6 MPa measured at the gas outlet of the reactor and at a temperature of 83° C. and was run in a monomodal setup with only barrier flushing.

[0133] The riser (5) had an internal diameter of 200 mm and a length of 19 m. The downcomer (6) had a total length of 18 m, an upper section of 5 m with an internal diameter of 300 mm and a lower section of 13 m with an internal diameter of 150 mm. The downcomer was fed with monomers at three points. At the feed point 1 (8), located directly below the barrier, 25 kg / h of liquid condensate (10), 10 kg / h of ethylene (9) and 900 g / h of 1-hexene (9) were introduced. At the feed point 2 (11), located 2.3 meters below the feed point 1, 15 kg / h of liquid condensate (13) and 5 kg / h of ethylene (12) were introduced. At the feed point 3 (14), located 4.0 meters below the feed point 2, 15 kg / h of liquid condensate (16) and 5 kg / h of ethylene (15) were introduced. 5 kg / h of propane, 33.4 kg / h of ethylene and 8 g / h of hydrogen were fed to the recycle system through line (19).

[0134] The liquid condensate that serves as the flashing means is obtained from a stream resulting from the condensation of the recycle stream (line 19).

[0135] The final polymer was discharged discontinuously via line (18).

[0136] The first reactor produced about 46 wt % (split wt %) of the total amount of final polyethylene resin produced by both the first and second reactors.

[0137] The final MIF of the resulting polyethylene polymer was 10.7 g / 10 min. The resulting density was 0.951 g / cm. 3 It was.

[0138] The amount of comonomer (hexene-1) was about 0.90 wt%.

[0139] Example 2 The conditions were identical to those in Example 1, except that 47 kg / h of ethylene, 150 g / h of hydrogen and 11 kg / h of propane were fed to the fluidized bed reactor (1) via line (3). The selected feed rates resulted in an ethylene concentration in the reactor of 6.6% by volume and a hydrogen / ethylene molar ratio in the reactor of 2.7.

[0140] The polyethylene obtained in the fluidized bed reactor (1) had an MIE of 99 g / 10 min and a viscosity of 0.968 g / cm 3 The density was 1.01 μm.

[0141] Monomers were fed to the downcomer at three points: at feed point 1 (8) 25 kg / h of liquid condensate (10), 10 kg / h of ethylene (9) and 450 g / h of 1-hexene (9) were introduced; at feed point 2 (11) 15 kg / h of liquid condensate (13) and 5 kg / h of ethylene (12) were introduced; at feed point 3 (14) 15 kg / h of liquid condensate (16) and 5 kg / h of ethylene (15) were introduced; 5 kg / h of propane, 34.8 kg / h of ethylene and 6.5 g / h of hydrogen were fed to the recycle system through line (19).

[0142] The liquid condensate that serves as the flashing means is obtained from a stream resulting from the condensation of the recycle stream (line 19).

[0143] The first reactor produced approximately 45 wt % (split wt %) of the total amount of final polyethylene resin produced by both the first and second reactors.

[0144] The final MIF of the resulting polyethylene polymer was 11.5 g / 10 min. The resulting density was 0.954 g / cm. 3 It was.

[0145] The amount of comonomer (hexene-1) was about 0.45 wt%.

[0146] Example 3 To carry out the polymerization, 10.5 g / h of solid catalyst and 0.21 g / h of tetrahydrofuran (THF) were fed to a first stirred pre-contact vessel using 1.5 kg / h of liquid propane, the conditions being identical to those in Example 1, except that triisobutylaluminum (TIBA) was also charged therein. The weight ratio of aluminum alkyl to Ziegler catalyst was 2:1.

[0147] 46 kg / h ethylene, 185 g / h hydrogen and 11 kg / h propane were fed to the fluidized bed reactor (1) via line (3). The selected feed rates resulted in an ethylene concentration in the reactor of 7.3% by volume and a hydrogen / ethylene molar ratio in the reactor of 3.4.

[0148] The polyethylene obtained in the fluidized bed reactor (1) had an MIE of 101 g / 10 min and a viscosity of 0.968 g / cm 3 The density was 1.01 μm.

[0149] The multi-zone circulation reactor (MZCR) was operated at a pressure of 2.6 MPa measured at the gas outlet of the reactor and a temperature of 85° C., and was run in a monomodal setup with barrier flushing only.

[0150] Monomers were fed to the downcomer at three points: at feed point 1 (8) 25 kg / h of liquid condensate (10), 9.5 kg / h of ethylene (9) and 500 g / h of 1-hexene (9) were introduced; at feed point 2 (11) 15 kg / h of liquid condensate (13) and 4.5 kg / h of ethylene (12) were introduced; at feed point 3 (14) 15 kg / h of liquid condensate (16) and 4.5 kg / h of ethylene (15) were introduced; 5 kg / h of propane, 31.8 kg / h of ethylene and 10 g / h of hydrogen were fed to the recycle system through line (19).

[0151] The liquid condensate that serves as the flashing means is obtained from a stream resulting from the condensation of the recycle stream (line 19).

[0152] The first reactor produced about 47 wt % (split wt %) of the total amount of final polyethylene resin produced by both the first and second reactors.

[0153] The final MIF of the resulting polyethylene polymer was 7.1 g / 10 min. The resulting density was 0.953 g / cm. 3 It was.

[0154] The amount of comonomer (hexene-1) was about 0.52 wt%.

[0155] Example 4 To carry out the polymerization, 12.5 g / h of the solid catalyst and 0.25 g / h of THF were fed to a first stirred pre-contact vessel using 1.5 kg / h of liquid propane, the conditions being identical to those in Example 1, except that triisobutylaluminum (TIBA) was also charged therein. The weight ratio of aluminum alkyl to Ziegler catalyst was 2:1.

[0156] 49.5 kg / h ethylene, 185 g / h hydrogen and 11 kg / h propane were fed to the fluidized bed reactor (1) via line (3). The selected feed rates resulted in an ethylene concentration in the reactor of 7.5% by volume and a hydrogen / ethylene molar ratio in the reactor of 3.2.

[0157] The polyethylene obtained in the fluidized bed reactor (1) had an MIE of 95 g / 10 min and a viscosity of 0.967 g / cm 3 The density was 1.01 μm.

[0158] The multi-zone circulation reactor (MZCR) was operated at a pressure of 2.6 MPa measured at the gas outlet of the reactor and a temperature of 85° C., and was run in a monomodal setup with barrier flushing only.

[0159] Monomers were fed to the downcomer at three points: at feed point 1 (8) 25 kg / h of liquid condensate (10), 9.5 kg / h of ethylene (9) and 1000 g / h of 1-hexene (9) were introduced; at feed point 2 (11) 15 kg / h of liquid condensate (13) and 4.5 kg / h of ethylene (12) were introduced; at feed point 3 (14) 15 kg / h of liquid condensate (16) and 4.5 kg / h of ethylene (15) were introduced; 5 kg / h of propane, 31.5 kg / h of ethylene and 8 g / h of hydrogen were fed to the recycle system through line (19).

[0160] The liquid condensate that serves as the flashing means is obtained from a stream resulting from the condensation of the recycle stream (line 19).

[0161] The first reactor produced about 49 wt % (split wt %) of the total amount of final polyethylene resin produced by both the first and second reactors.

[0162] The final MIF of the resulting polyethylene polymer was 10.0 g / 10 min. The resulting density was 0.951 g / cm. 3 It was.

[0163] The amount of comonomer (hexene-1) was about 1.0 wt%.

[0164] Comparative Example 1 Polyethylene was produced in a cascade of a fluidized bed reactor and a multi-zone circulating reactor having two interconnected reaction zones as shown in FIG.

[0165] To carry out the polymerization, 10.8 g / h of solid catalyst prepared as described in Example 1 of WO2016206958 were fed using 1.1 kg / h of liquid propane to a first stirred pre-contact vessel, which was also charged with triisobutylaluminum (TIBA), diethylaluminum chloride (DEAC). The weight ratio of triisobutylaluminum and diethylaluminum chloride was 7:1. The weight ratio of aluminum alkyl to Ziegler catalyst was 5:1. The first pre-contact vessel was maintained at 50° C. with an average residence time of 30 minutes. The catalyst suspension of the first pre-contact vessel was continuously transferred to a second stirred pre-contact vessel, which was operated with an average residence time of 30 minutes and was also maintained at 50° C. The catalyst suspension was continuously transferred to a fluidized bed reactor (FBR) (1) via line (2).

[0166] Ethylene was polymerized in the presence of propane as inert diluent in a fluidized bed reactor (1) using hydrogen as molecular weight regulator. 50 kg / h ethylene, 235 g / h hydrogen and 11 kg / h propane were fed to the fluidized bed reactor (1) via line (3). No comonomer was added. The polymerization was carried out at a polymerization temperature of 80° C. and a pressure of 3.0 MPa. The selected feed rates resulted in an ethylene concentration of 9.9% by volume in the reactor and a hydrogen / ethylene molar ratio of 2.6 in the reactor.

[0167] The polyethylene obtained in the fluidized bed reactor (1) had an MIE of 91 g / 10 min and a viscosity of 0.967 g / cm 3 The density was 1.01 μm.

[0168] The polyethylene obtained in the fluidized bed reactor (1) was continuously transferred to a multi-zone circulation reactor (MZCR), which was operated at a pressure of 2.6 MPa and a temperature of 80 °C measured at the gas outlet of the reactor, and was run in a monomodal setup with only barrier flushing. The riser (5) had an internal diameter of 200 mm and a length of 19 m. The downcomer (6) had a total length of 18 m, an upper part of 5 m with an internal diameter of 300 mm and a lower part of 13 m with an internal diameter of 150 mm. The downcomer was fed with monomer at three positions. At the input point 1 (8), located just below the barrier, 25 kg / h of liquid condensate (10), 10 kg / h of ethylene (9) and 1000 g / h of 1-hexene (9) were introduced. At feed point 2 (11), located 2.3 meters below feed point 1, 15 kg / h of liquid condensate (13) and 5 kg / h of ethylene (12) were introduced. At feed point 3 (14), located 4.0 meters below feed point 2, 15 kg / h of liquid condensate (16) and 5 kg / h of ethylene (15) were introduced. 5 kg / h of propane, 30.0 kg / h of ethylene and 5 g / h of hydrogen were fed to the recycle system via line (19).

[0169] The liquid condensate that serves as the flashing means is obtained from a stream resulting from the condensation of the recycle stream (line 19).

[0170] The final polymer was discharged discontinuously via line (18).

[0171] The first reactor produced about 49 wt % (split wt %) of the total amount of final polyethylene resin produced by both the first and second reactors.

[0172] The final MIF of the resulting polyethylene polymer was 8.7 g / 10 min. The resulting density was 0.951 g / cm. 3 It was.

[0173] The amount of comonomer (hexene-1) was about 1.0 wt%.

[0174] [Table 2] Note: C2H4 = ethylene; C6H 12 = hexene; amounts of ethylene and hexene are volume percent; split = weight of polymer produced in the reactor; * neck height: 8DD, BUR: 4:1, speed = 72 kg / h, film thickness = 12.5 μm.

Claims

1. A polyethylene composition comprising: A) Density determined according to ISO 1183-1:2012 at 23°C is 0.960 g / cm 3 %. 30 to 70 wt. % ethylene homopolymer having a melt flow index (MIE) of 130 g / 10 min or less, measured at 190° C. under a load of 2.16 kg according to ISO 1133-2:2011; B) 30 to 70 weight percent of an ethylene copolymer having an MIE value lower than that of A), the copolymer comprising ethylene and a comonomer of hexene-1; The amounts of A) and B) are based on the total weight of A)+B); The polyethylene composition has the following characteristics: 1) 0.948-0.960 cm, measured according to ISO 1183-1:2012 at 23 °C 3 density of; 2) a MIF / MIP ratio of 20 to 40, where MIF is the melt flow index at 190°C under a load of 21.60 kg and MIP is the melt flow index at 190°C under a load of 5 kg, both measured according to ISO 1133-2:2011; 3) MIF 6-15 g / 10 min; 4) HMWcopo index between 0.5 and 3.3; 5) Long-Chain Branching Index (LCBI) less than or equal to 0.72; The HMWcopo index is determined according to the following formula: HMWcopo = (η 0.02 x t maxDSC ) / (10^5) In the above formula, η 0.02 is the complex viscosity (Pa.s) of the melt measured at a temperature of 190°C on a parallel plate rheometer in dynamic oscillatory shear mode with an applied angular frequency of 0.02 rad / s; t maxDSC is the time (in minutes) required to reach the maximum value of the heat flow of crystallization at a temperature of 124° C. under quiescent conditions measured in isothermal mode in a differential scanning calorimetry apparatus; LCBI is the measured mean square radius of gyration R measured by GPC-MALLS at a weight average molecular weight (Mw) of 1,000,000 g / mol. g to the mean square radius of gyration for a linear PE having the same weight average molecular weight (Mw); 6) η 0.02 is less than or equal to 125000, A monolayer blown film of said polyethylene composition having a thickness of 12.5 μm has a blown film bubble stability score (BSS) of 52 or greater when the Dart Drop Index (DDI) value is between 200 and 350 g, and a BSS score of 40 or greater when the DDI value is greater than 350 g, as measured according to ASTM D1709, Method A.

2. 2. The polyethylene composition according to claim 1, obtained using a Ziegler-Natta polymerization catalyst.

3. The polyethylene composition of claim 2, wherein the Ziegler-Natta polymerization catalyst comprises the reaction product of: a) a) b) a) a) MgCl 2 a prepolymerized solid catalyst component comprising a Ti compound supported thereon; b) an organoaluminum compound; and optionally c) An external electron donor compound.

4. 2. The polyethylene composition of claim 1 having at least one of the following additional characteristics: - Ethylene homopolymer A) has a density of 0.960 to 0.971 g / cm 3 ; - Eta divided by 1000 0.02 and the LCBI, the ratio (η 0.02 / 1000) / LCBI is 120-180; - 200000 to 400000 M w value; - 25 to 65 M w / M n value; - the comonomer content is less than or equal to 2% by weight, based on the total weight of the composition (as determined by IR); - ER value between 2 and 5; - ET value ≤ 25; Here, ER is calculated by the following formula: IS = (1.781*10 -3 )*G' G''=5,000 dyn / cm 2 With the value of ET is calculated according to the following formula: tan δ = C 3 ET = C 2 / G* Where: G* = [(G') 2 + (G'') 2 ] 1 / 2 ; tan δ = G′′ / G′; C 2 = 10 6 dyn / cm 2 and C 3 = 1.5 G' = storage modulus; G” = loss modulus; Both G' and G" are measured by dynamic oscillatory shear in a plate-plate rotational rheometer at a temperature of 190°C; - Long Chain Branching Index (LCBI) is less than or equal to 0.

70.

5. 13. An article of manufacture comprising the polyethylene composition of claim 1.

6. 6. The article of manufacture of claim 5, in the form of a single or multi-layer blown film, at least one layer comprising the polyethylene composition of claim 1.

7. 7. The breathable film of claim 6, wherein a monolayer breathable film of said polyethylene composition having a thickness of 12.5 μm has a Bubble Stability Score (BSS) of 52 or more for Dart Drop Index (DDI) values ​​of 200 to 350 g, measured according to ASTM D1709, Method A, while the BSS score is 40 or more for DDI values ​​of more than 350 g.

8. All polymerization steps were treated with MgCl 2 2. A process for producing the polyethylene composition according to claim 1, conducted in the presence of a Ziegler-Natta polymerization catalyst supported thereon.

9. 9. The method of claim 8, comprising the following steps, in any mutual order: a) polymerizing ethylene, optionally with one or more comonomers, in a gas phase reactor in the presence of hydrogen; b) copolymerizing ethylene with one or more comonomers in a separate gas phase reactor in the presence of less hydrogen than in step a); Here, in at least one of the gas-phase reactors, the growing polymer particles flow upwards under fast fluidization or transport conditions through a first polymerization zone, and after leaving the first polymerization zone, enter a second polymerization zone, through which they flow downwards under the action of gravity, and after leaving the second polymerization zone, are again introduced into the first polymerization zone, thereby establishing a polymer circulation between the two polymerization zones.

Citation Information

Patent Citations

  • Multimodal polyethylene composition for manufacturing pipes with improved resistance to slow crack growth

    JP2014534330A

  • Polyethylene composition having a high swell ratio

    JP2015532349A

  • Polyethylene composition for film

    JP2018518579A

  • Polyethylene type resin and method for producing the same, and inflation film using the same as base material

    US20040236041A1

  • Polyethylene type resin and method for producing the same, and inflation film using the same as base material

    WO2003004539A1